Tobacco Institute 1994 Public Affairs Buget, [Memos from Susan Stuntz] - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Memos from Susan Stuntz to Cal George and to Samuel Chilcote, Jr and Tobacco Institute 1994 Public Affairs budget. Adresses a speech in front of House Republicans opposing cigarette tax. Attributes increased budget needs to pressure on the advertising front and increased reliance on outside consultants. Summarizes cost centers as general administration, scientific research regarding public smoking, media relations, excise taxes/social costs, general coalitions, and advertising/youth issues.